Investigating the ability of coral reefs to protect shorelines in the Republic of Kiribati - Summers, Heather E.; Donner, Simon D. (Coral reefs, 2022)
The three-dimensional (3D) structure of living coral communities provides frictional resistance to waves and currents. Coral bleaching events can lead to a shift in coral assemblages toward stress-tolerant colonies, potentially reducing reef structural complexity and, in turn, wave attenuation. This is a particular concern in low-lying coastal regions at risk from sea-level rise. In this study, we examined trade-offs between reef resilience and reef structural complexity (defined into three distinct variables, i.e., surface rugosity, standard deviation of elevation, and terrain ruggedness) in Kiribati’s Tarawa and Abaiang Atolls, which are subject to frequent El Niño-driven heat stress. Analysis of benthic cover data and 3D reconstructions of the fore reefs indicate that structural complexity increases with coral cover, rather than coral diversity, although the relationship depends on the metric used and on the morphology of the dominant coral species. Contrary to expectations, surface rugosity and standard deviation of elevation were not significantly different between the bleaching-resistant reefs of South Tarawa, dominated by the encrusting species Porites rus , and the more diverse sites in Abaiang and North Tarawa; terrain ruggedness was significantly greater at South Tarawa sites. A wave attenuation model, however, suggested that wave energy may nonetheless be higher in South Tarawa due to years of local mining of reef rock from the reef flat. Taken together, the results suggest that the survival of stress-tolerant corals could mitigate against losses of structural complexity from repeated bleaching events. These findings illustrate the need for more research bridging ecology and geology to establish how wave attenuation is altered by climate-driven regime shifts on coral reefs.